2005
DOI: 10.1038/oby.2005.63
|View full text |Cite
|
Sign up to set email alerts
|

Alleles on Rat Chromosome 4 (D4Got41‐Fabp1/Tacr1) Regulate Subphenotypes of Obesity

Abstract: KLÖ TING, NORA, BARBARA WILKE, AND INGRID KLÖ TING. Alleles on rat chromosome 4 (D4Got41-Fabp1/ Tacr1) regulate subphenotypes of obesity. Obes Res. 2005; 13:589 -595. Objective: The use of inbred animal models is an essential component of the genetic dissection of complex diseases. Because quantitative trait loci for serum triglycerides, total cholesterol, and body weight were mapped on chromosome 4 in a cross of BioBreeding/OttawaKarlsburg (BB/OK) and spontaneously hypertensive (SHR) rats, we established a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Retinol-binding protein 4 (RBP4), a protein released from adipocytes and associated with obesity and insulin resistance, is preferentially produced by VAT and is a marker of intra-abdominal adipose tissue expansion [172]. Plasminogen activator inhibitor 1 (PAI1), an inhibitor of fibrinolysis, is strongly up-regulated in VAT depots, and plasma levels correlate with trunk fat mass in obesity [173], suggesting a plausible link between obesity and thrombotic disorders [174].…”
Section: Secretory Functionmentioning
confidence: 99%
“…Retinol-binding protein 4 (RBP4), a protein released from adipocytes and associated with obesity and insulin resistance, is preferentially produced by VAT and is a marker of intra-abdominal adipose tissue expansion [172]. Plasminogen activator inhibitor 1 (PAI1), an inhibitor of fibrinolysis, is strongly up-regulated in VAT depots, and plasma levels correlate with trunk fat mass in obesity [173], suggesting a plausible link between obesity and thrombotic disorders [174].…”
Section: Secretory Functionmentioning
confidence: 99%
“…The phenotypic characterization of both congenic strains termed BB.4S (D4Got41-Tracr1; 60.5-122.8 Mb) and BB.4W (D4Got41-Fabp1; 60.5-104.6 Mb) showed that the strains develop obesity, dyslipidemia, hyperleptinemia (BB.4S) or hyperinsulinemia (BB.4W) compared with parental strain BioBreeding/OttawaKarlsburg (BB/OK). In contrast to parental BB/OK rats developing type 1 diabetes at a frequency of more than 86% [7], none of the congenic BB.4S [8], and BB.4W [6] rats developed diabetes. All congenic rats remained normoglycemic up to an age of 30 weeks, which was attributable to the lack of diabetogenic gene Iddm2 (Gimap5), an essential gene for type 1 diabetes development in BB/OK rats.…”
Section: Introductionmentioning
confidence: 76%
“…In contrast to their parental strain BB/OK, congenic BB.4S and BB.4W do not develop type 1 diabetes, but they manifest facets of metabolic syndrome [6]. Because BB.4S and BB.4W showed comparable facets of metabolic syndrome, it was not surprising that both congenic strains differed in the relative expression of selected genes when compared with their parental BB/OK strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many QTLs not related to neurobiological traits were identified on rat Chr. 4, such as for bone mineral density [57], blood pressure [58] and body weight [59], among others [23]. These findings suggest that Chr.…”
Section: Rat Chromosome 4 and Its Neurobiological-related Qtlsmentioning
confidence: 92%